1997
DOI: 10.1046/j.1471-4159.1997.68062348.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1 Enhances Induction by Nerve Growth Factor of a Putative Dimer of TrkA

Abstract: GM1 enhances nerve growth factor (NGF)-stimulated neuritogenesis and prevents apoptotic death of PC12 cells; both may be due to enhancement of TrkA dimerization. In this study, we examined the effect of GM1 on NGF-induced TrkA dimerization in Trk-PC12 (6-24) cells. NGF increased tyrosine phosphorylation of the 140-kDa protein (TrkA monomer), and preincubation with GM1 potentiated this effect. Adding the protein crosslinker bis(sulfosuccinimidyl) suberate with NGF resulted in the appearance of two major bands (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 30 publications
5
66
0
1
Order By: Relevance
“…We should note that previous reports have suggested that ganglioside G M1 induces Trk phosphorylation by itself and that it potentiates NGF-induced TrkA phosphorylation (Ferrari et al, 1995;Mutoh et al, 1995;Farooqui et al, 1997). We were able to detect a modest increase in TrkB phosphorylation in response to ganglioside G M1 only after high exposure of the autoradiography films (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…We should note that previous reports have suggested that ganglioside G M1 induces Trk phosphorylation by itself and that it potentiates NGF-induced TrkA phosphorylation (Ferrari et al, 1995;Mutoh et al, 1995;Farooqui et al, 1997). We were able to detect a modest increase in TrkB phosphorylation in response to ganglioside G M1 only after high exposure of the autoradiography films (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…In particular, a striking correlation between ganglioside expression and neuritogenesis has previously been established (Hogan et al, 1988;Rosenberg et al, 1992). The regulatory role of such lipids is usually attributed to their ability to form microdomains in cell membranes (Masserini et al, 1988), allowing for selective sorting of polarized neuronal structures (Hogan et al, 1988;van Echten and Sandhoff, 1989) or for dimerization-induced activation of growth factor receptors (Farooqui et al, 1997). It has been proposed that biochemical engineering of the side chain sialic acid might activate β1 integrins thus increasing binding to ECM molecules and favoring neuritogenesis (Buttner et al, 2002).…”
Section: Figmentioning
confidence: 99%
“…In addition, it has been postulated that GM1 may activate TrkA by inducing receptor dimerization (40). To test whether either one of these mechanisms may account for the ability of GM1 to induce Trk tyrosine phosphorylation, NIH-3T3 cells were transfected with an expression vector containing p70 trk , a chimeric receptor consisting of the extracellular domain of the TNF receptor and the transmembrane and intracellular domains of TrkA (36).…”
Section: Fig 1 Gm1 Activates Trk Tyrosine Phosphorylation Niha (A)mentioning
confidence: 99%